(untitled) (Revista Espacio Regional, 2021)
In rural areas of Mexico, the marginal conditions have increased, the rural support programs, welfarist and vertical, have failed to respond. An alternative to solve it, represents family farming and rescue knowledge and awareness of rural people. The stated objective is to raise awareness of women’s groups on nutritional importance of plants they have in their plots (backyard) and their potential contribution to food security and nutrition. With the participant group, the backyard are crossed, plants and animals that have consumed and are identified as, conducting a knowledge sharing. Participatory workshops on the basic principles of human nutrition known, the nutritive content of the products of the backyard and the design and development of balanced dishes (wise). It has worked in communities in the states of Oaxaca, Tabasco and Veracruz, with the participation of academic institutions, NGOs and government organizations. They have documented inventories of agro-biodiversity of backyard and recipes of dishes made. In working with people, a real process of knowledge exchange is established, all learn from all recognizing the own knowledge, allowing reaffirm and share. We conclude that the most important has been the consolidation of teams that have enabled the training of human resources on the importance of food sovereignty and food and nutrition security, contributing to the creation of local food systems.